2004
DOI: 10.1046/j.1439-0523.2003.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability for seed oil content and seed index in some wild species and perennial races of cotton

Abstract: A 3‐year study was made on genetic variability of seed oil content and seed index with 20 wild species, two cultivated species and six perennial races of Gossypium arboreum cotton maintained at the Central Institute for Cotton Research, Nagpur, India. The mean seed oil content varied from 10.26 to 22.89% in 22 species of Gossypium and six races of G. arboreum. In this material the weight of delinted seed varied from 43.33 to 54.54 mg/seed. The highest seed oil content was recorded in the species G. lobatum fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…The oil content in parents ranged from 17.7 (%) to 22.1 in F 1861 Pandey (1977) reported that the variability for oil content in improved strains of G. hirsutum ranged from 14.5 to 22.0% with mean of 19.2% (Table 5). The earlier workers, Dani (1989), Dani (1991), Gotmare et al (2004), Khan et al, (2007a) and Sharma et al, (2009) similar findings, and supported our results. Hassan et al (2005) studies exhibited the performance of Egyptian cotton cultivars for cottonseed oil percentage and found significant mean differences.…”
Section: Genetic Variability In F 1 Hybrids and Their Parentssupporting
confidence: 93%
“…The oil content in parents ranged from 17.7 (%) to 22.1 in F 1861 Pandey (1977) reported that the variability for oil content in improved strains of G. hirsutum ranged from 14.5 to 22.0% with mean of 19.2% (Table 5). The earlier workers, Dani (1989), Dani (1991), Gotmare et al (2004), Khan et al, (2007a) and Sharma et al, (2009) similar findings, and supported our results. Hassan et al (2005) studies exhibited the performance of Egyptian cotton cultivars for cottonseed oil percentage and found significant mean differences.…”
Section: Genetic Variability In F 1 Hybrids and Their Parentssupporting
confidence: 93%
“…Till date, it has been a challenging task to simultaneously improve oil content and yield in cotton (Gotmare et al. , Khan et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on phenotypic evaluation of the oil contents and agronomic traits in cotton were reported (Gotmare et al. , Meredith et al. ).…”
mentioning
confidence: 99%
“…Differentiation between the hair types has been maximised to produce the white lint in elite cultivars. Cottonseed oil accumulates in the cytoplasm of the seed embryo cells (Gotmare et al, 2004); it is not associated with the gossypol glands. Descriptions of the seed are provided by Hopper and McDaniel (1999) and Ritchie et al (2007), and an overview of advances in knowledge of the development of seed and fibre is provided by Ruan (2005).…”
Section: Descriptionmentioning
confidence: 99%